External Cephalic Version in Cases of Imminent Delivery at Preterm Gestational Ages: A Prospective Series - Meghan G. Hill; Kathryn L. Reed (Thieme Medical Publishers, Inc., 2019)
Objective When delivery of a breech fetus is required at a preterm gestational age, Cesarean delivery is often recommended. We performed a prospective patient series to assess the success rate and safety of performing external cephalic version (ECV) procedures on preterm fetuses as an alternative to Cesarean delivery. Study Design We performed a prospective clinical series of patients who required delivery with a malpresenting fetus at a preterm gestational age. Results ECV procedures were successful in singletons 50% of the time. No significant complications or cases of fetal mortality were documented. Conclusion ECV at preterm gestational ages may be an appropriate approach to management in patients requiring delivery. Larger series are needed to further document success rates and risks of the procedure.